The number of implants required to support a maxillary overdenture: a systematic review and meta-analysis. Issue 1 (January 2019) - Di Francesco, Fabrizio; De Marco, Gennaro; Gironi Carnevale, Ugo Antonello; Lanza, Michele; Lanza, Alessandro
Abstract: Purpose: The number of implants needed to support a maxillary overdenture is still a controversial issue. The aim of this systematic review was to investigate the number of implants required to support a maxillary overdenture in order to obtain optimal treatment outcomes in terms of implant survival, overdenture longevity and patient satisfaction. Study selection: Pubmed and EMBASE databes were systematically searched and complemented by hand searching from 2000 to 2017. The Prisma statement and a PICOS approach were adopted. All selected articles provided at least two-year follow-up and 10 totally edentulous patients. Survival rate of implants and overdentures were statistically analyzed according to number of implants and according to splitting technique, employing non-parametric Fisher Test for unpaired data. For the pooled analysis of implant failures, the odds ratio between group of 4 splinted implants and group of more than 4 splinted was calculated. Results: A total of 28 articles were included. Data analysis of the included studies showed that the survival rate of implants appeared higher in ≥ 4 implants group, whereas the high survival rate of overdentures and patient satisfaction were not significantly influenced by the number of implants. Conclusions: The findings of our analysis indicate that overall the most frequent tendency is to place at least four implants, splinted or unsplinted, in order to ensure a higher survival rate of implants. However, the relationship between overdenture survival, the patient's quality of life, and the number of implants required to support a maxillary overdenture has yet to be clarified.